Pelatihan Pembuatan Media Pembelajaran Berbasis Website Terintegrasi Model Pembelajaran Project Based Learning bagi Guru SMAN 2 Tondano Minahasa - Kamaruddin Kamaruddin; Patricia Mardiana Silangen; Djeli Alvi Tulandi (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase knowledge and competence in creating website-based learning media integrated with the project-based learning (PjBL) learning model for teachers at SMAN 2 Tondano, Minahasa Regency. Implementing this service used training, which included lectures, discussions, simulations, and mentoring. The activity evaluation instrument used a questionnaire and was analyzed descriptively. The results of this service showed that the ability of ICT teachers at SMAN 2 Tondano increased in creating website-based learning media integrated with the PjBL model. The implementation of training and mentoring activities received a positive response from participants, as evidenced by the enthusiasm and activeness of teachers in participating in the training. The evaluation results showed that the level of satisfaction and increase in teacher knowledge after participating in the training was in the very good category. Teachers were very interested in using website-based learning media because of its advantages and integration with the PjBL learning model.